The medical impact of hepatitis D virus infection in Asia and Africa; time for a reappraisal - Rizzetto, Mario; Hamid, Saeed (Liver international, 2021)
Although hepatitis D is believed to be an important medical problem in Africa and many areas of Asia, the geographical distribution and prevalence rates of infection with the hepatitis D virus (HDV) vary considerably, are often inconsistent and sometimes conflicting. Discrepancies may depend on methodological problems, primarily on different modalities of patients' recruitment; these are analysed in this mini‐review, in order to provide a uniform clinical approach when testing patients with chronic HDV disease.